Correlation of histopathologic findings with clinical predictors of disease recurrence and progression to vulvar carcinoma in patients with differentiated vulvar intraepithelial neoplasia (dVIN) - Jill N.T. Roberts; Jessica L. Bentz; Robert E. LeBlanc; Ilana Cass (Gynecologic Oncology Reports, 2024)
Objective: To evaluate predictors of recurrence and the risk of progression to carcinoma in patients with dVIN. Methods: 36 self-identified White patients with dVIN from 2011 to 2022 were identified. Demographics, treatment and clinical course were abstracted. Histopathologic features and IHC stains were reviewed by 2 subspecialty pathologists. Standard statistical analyses were applied. Results: Median cohort age was 70 years (range 39–91). Median follow-up was 29.5 months (range 1–123). All patients were Caucasian. 67% had lichen sclerosus (LS) adjacent to dVIN. 56% of patients had recurrent dVIN a median of 11 months from diagnosis. 14 patients had invasive squamous cell carcinoma of the vulva (SCCV) during the study period: 9 (25%) with synchronous dVIN, 5 (14%) developed SCCV after a median of 21.5 months (range 8–57). Patients treated with surgery were more likely to have recurrent/persistent dVIN (p = 0.04) and synchronous or progression to SCCV (p = 0.02) than patients treated with topical therapy. Excluding 9 women with synchronous SCCV, no initial treatment (observation, topical therapy, surgery) was superior at preventing recurrent/ progressive disease in isolated dVIN. Mutation-type p53 expression was identified in 18 (64%) and aberrant GATA3 staining/expression in 20 (56%) of cases. Aberrant GATA3 expression was associated with a higher frequency of synchronous/progression to SCCV (p < 0.05). Conclusion: dVIN has an aggressive clinical course in white patients with a high risk of recurrence/persistence and synchronous/progression to SCCV despite treatment. Close surveillance with a low threshold for additional biopsies is warranted. P53 and GATA3 IHC stains may be useful markers of disease outcome.